New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Finestone, EM; Plummer, TW; Vincent, TH; Blumenthal, SA; Ditchfield, PW; Bishop, LC; Oliver, JS; Herries, AIR; Palfery, CV; Lane, TP; McGuire, E; Reeves, JS; et al. (Elsevier, 2024)
The Homa Peninsula, in southwestern Kenya, continues to yield insights into Oldowan hominin landscape behaviors. The Late Pliocene locality of Nyayanga (∼3–2.6 Ma) preserves some of the oldest Oldowan tools. At the Early Pleistocene locality of Kanjera South (∼2 Ma) toolmakers procured a diversity of raw materials from over 10 km away and strategically reduced them in a grassland-dominated ecosystem. Here, we report findings from Sare-Abururu, a younger (∼1.7 Ma) Oldowan locality approximately 12 km southeast of Kanjera South and 18 km east of Nyayanga. Sare-Abururu has yielded 1754 artifacts in relatively undisturbed low-energy silts and sands. Stable isotopic analysis of pedogenic carbonates suggests that hominin activities were carried out in a grassland-dominated setting with similar vegetation structure as documented at Kanjera South. The composition of a nearby paleo-conglomerate indicates that high-quality stone raw materials were locally abundant. Toolmakers at Sare-Abururu produced angular fragments from quartz pebbles, representing a considerable contrast to the strategies used to reduce high quality raw materials at Kanjera South. Although lithic reduction at Sare-Abururu was technologically simple, toolmakers proficiently produced cutting edges, made few mistakes and exhibited a mastery of platform management, demonstrating that expedient technical strategies do not necessarily indicate a lack of skill or suitable raw materials. Lithic procurement and reduction patterns on the Homa Peninsula appear to reflect variation in local resource contexts rather than large-scale evolutionary changes in mobility, energy budget, or toolmaker cognition.